Recent Patents on Detection of Bearing Temperature - Zhao, Yanling; Zhang, Jiashuo (Recent Patents on Engineering, 2022)
Background: One of the critical factors affecting the life of bearings is the bearing temperature during operation, so the temperature is an important parameter to detect the running state of the bearing. The abnormal increase in bearing temperature can reflect problems such as bearing damage, lack of lubricating oil, and installation errors. With the continuous improvement of rotating machinery equipment operating speed, load level and equipment processing accuracy requirements, there is an urgent need to detect and analyze the temperature rise of bearings. Objective: By analyzing recent representative patents for bearing temperature detection, we summarize the characteristics and problems of current bearing temperature detection devices and provide a reference for the future development of bearing temperature detection devices. Methods: This article traces the recent representative patents related to bearing temperature detection method and device structure. Results: Through the investigation of a large number of patents of bearing temperature detection devices, the main existing problems in the system and structure of bearing temperature detection are concluded and analyzed, and the development of bearing temperature detection is discussed in the future. Conclusion: The bearing temperature measuring device is significant for analyzing bearing heating and detecting the running state of the bearing. The current research results need further development and improvement. With the development of automated detection technology, bearing temperature measurement is also evolving towards intelligence and dynamics. It is foreseeable that more related patents on bearing temperature detection will be invented.
Keywords: spindle